Revisiting the Causal Effect of Education on Political Participation and Interest - Nadja Bömmel; Guido Heineck (Institute of Labor Economics (IZA), 2020)
A substantial number of studies suggests a strong relationship between education and aspects of political participation and interest. Only a small body of literature, however, addresses whether these patterns represent causal effects. We add to this research and re-examine the question in the German context. For identification, we exploit an exogenous increase in lower secondary compulsory schooling between 1949 and 1969 in former West Germany, and use data from the National Educational Panel Study (NEPS) to identify individuals' educational biographies more precisely than prior research. Our results reinforce findings from Siedler (2010): multiple regression analyses first indicate a positive, statistically significant correlation between schooling and our measures of political activities. IV estimates, however, are all trivial, for both compliers and the full sample, indicating that the reform did not stimulate long-term changes in political participation and interest.
Keywords: I2; H4; H23; 330; school reform; political participation; IV estimation; returns to education; Germany